No evidence that timber harvesting increased the scale or severity of the 2019/20 bushfires in south-eastern Australia. Issue 3 (3rd July 2021) - Keenan, R. J.; Kanowski, P.; Baker, P. J.; Brack, C.; Bartlett, T.; Tolhurst, K.
ABSTRACT: In the summer of 2019/20, bushfires of unprecedented scale in south-eastern Australia focused attention on how forest management might have affected their risks and impacts. Some argued that the severity and extent of these fires were made worse by timber harvesting and associated forest management and that harvesting in native forests should cease as a means for reducing fire risk. Little evidence has been presented to support these contentions. This article reviews evidence for the relationship between harvesting and fire extent and severity from these fires. The proportion of forested conservation reserves burnt in these fires was similar to that for public forests where timber harvesting is permitted, and the proportion of forest burnt with different levels of fire severity was similar across tenures and over time since timber harvest. Recent analysis of the areas burnt in 2019/20 indicated that the extent and severity of the fires was determined almost entirely by three years of well-below-average rainfall (leading to dry fuels across all vegetation types), extreme fire weather conditions and local topography and that past timber harvesting had negligible or no impact on fire severity. Three major inquiries into the fires made no recommendations regarding the impact of timber harvesting on fire risk. We argue that policy proposals to mitigate fire risk and impacts should be evidence-based and, to avoid the cognitive bias associated with expert opinions, should integrate the multiple perspectives of traditional Indigenous knowledge, the experience of local and professional fire managers, and the breadth of evidence from bushfire research. Together, these perspectives should inform strategies for reducing bushfire impacts and increasing forest resilience and community safety.